Responsible tourism - Pathway to realizing sustainable development: Introduction to responsible tourism and its implementation in the ASEAN - Phuong, Bui Thi Ngoc (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The concept of sustainable tourism first emerged in 1992. After more than 30 years on a journey towards establishing sustainable values, we have shown signs of perplexity in various aspects, focusing on issues such as: whose responsibility it is, how it should be implemented, and how it can be measured. Although each country has demonstrated efforts to minimize the impact of tourism on life across three dimensions: economic, environmental, and social. It must be acknowledged that these relentless efforts reflect a high sense of responsibility from governments and organizations. However, it seems the process of protecting the environment and human life is weaker than the rate of tourism development. We need to clarify more about who is responsible and how in this global campaign. Responsible tourism emerged in 2002 and became stronger after the COVID-19 pandemic as a global revolution for the tourism industry. Utilizing qualitative research methods: data collection and processing, case study, observation, and interviewing, this article (the first part) delves into the core aspects of responsible tourism as a strategic direction for achieving sustainability in the tourism sector. Furthermore, the paper summarizes the application of Responsible Tourism in some Southeast Asian countries in recent times.